PERAN PENGADILAN DALAM PROSES EKSEKUSI PUTUSAN YANG BERKEKUATAN HUKUM TETAP DI PENGADILAN TATA USAHA NEGARA SEMARANG - Pratama Herry Herlambang; Tri Sulistiyono; Faridhotun Ridho (Universitas Negeri Semarang, 2020)
The State Administrative Court (PTUN) is a place to find the real truth about the actions of state administrative officials that are not under the General Principles of Good Governance (AAUPB), for people whose interests and rights are taken away by parties who are deemed to be acting arbitrarily against other parties. The decisions that have been produced during the proceedings at the PTUN will undoubtedly have an impact which is expected to make a positive contribution in formulating a system of legal protection that is just, harmonious, and under the State Administrative Court Law and the 1945 Constitution of the Republic of Indonesia as the basis of the Indonesian state.